Pengaruh Kualitas Pelayanan Bus Listrik Terhadap Minat Masyarakat Kota Medan dalam Menggunakan Transportasi Umum - Siboro, Noviyanti Godelifa G.; Ginting, Simson (Universitas Pahlawan Tuanku Tambusai, 2025)
Global Warming is a concern for the world today because of the significant climate change phenomenon felt by the world's population. One of the adverse impacts is poor air quality. Based on various reports on environmental conditions, air quality is the second highest cause of death in the world. One way that has been done is to improve the use of energy in transportation systems to renewable energy such as electric buses. The problem that exists in achieving the objectives of the method is how the community responds to the services provided by the government in this renewable transportation system.This study aims to provide empirical results regarding the effect of service quality from the Medan City Transportation Agency on public interest in using electric bus transportation services. The theory used is Service Quality (SERVQUAL) from Parasuraman and The Planned Behavior from Icek Ajzen. The method used is quantitative method with associative research type. The research respondents were 89 people. Data collection techniques using questionnaires and field observations. The data analysis used includes validity test, reliability test, descriptive statistical analysis test, normality test, linearity test, and hypothesis testing using simple linear regression test, correlation coefficient test (r test), determination coefficient test (r2) and partial significance test (t test). Processing of this questionnaire data using SPSS version 26 software. The results showed that there is a positive relationship between service quality and public interest. The results of the linear test with a value of 0.156 which means that there is a linear relationship between variables X and Y. The results of the simple linear regression test of the service quality variable (X) with a regression coefficient (b) of 0.422, a constant value (a) of 8.186. The result of the correlation coefficient (r test) is 0.873 and the coefficient of determination test is 0.762 which can be concluded that the two results are included in a very strong relationship, and based on the results of the coefficient of determination test, there is an influence of the service quality variable (X) on public interest (Y) of 76.2%.